Teacher’s Practices in Developing Vocabulary through Flashcards and Coloring - Ghefira Faiz Sabila (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2026)
English is taught as a foreign language in Thailand, and many primary school students experience difficulties in mastering vocabulary, which affects their participation in English learning. This study aimed to explore English teacher practices in developing students’ vocabulary mastery using flashcards and coloring activities at Ban Bangoisinae Thailand Primary School. The research focused on how the teacher planned, implemented, and evaluated vocabulary instruction for young learners. This study employed a qualitative case study design. The participant was one English teacher selected through purposive sampling. Data were collected through classroom observation, interviews, and document analysis, and were analyzed using data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that in the planning stage, the teacher identified students’ proficiency levels, selected simple vocabulary topics, and prepared visual materials such as picture flashcards and coloring worksheets. In the implementation stage, vocabulary teaching was carried out through structured activities including vocabulary introduction, practice, coloring tasks, and review. Evaluation was conducted through informal classroom assessment and formal writing tests. The study concludes that flashcards and coloring activities effectively support vocabulary learning by increasing students’ motivation, understanding, and retention in an enjoyable learning environment.